Close encounters of the third kind [videorecording (DVD)] - Spielberg, Steven, 1946-; Dreyfuss, Richard (Columbia TriStar Home Entertainment, 2002)
Roy Neary witnesses the arrival of a flying saucer from an alien world. Thus begins an incredible series of events, culminating in the ultimate encounter with other-worlders as Neary is led aboard the awesome Mothership.